TRENDS AND PROSPECTS OF THE DEVELOPMENT OF THE HOTEL AND RESTAURANT BUSINESS IN UKRAINE - MAMONTENKO, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Among business entities in the hotel and restaurant sector of Ukraine, the largest specific weight was small enterprises that worked in quick service establishments. In recent years, the number of food establishments operating in shopping and entertainment centers has increased. Before the beginning of the full-scale invasion and the pandemic, the growth of the sector was associated with the growth of incomes of citizens, and the resulting growth of solvent demand. The main limitations that hindered the development of enterprises include the relatively low profitability of the hotel and restaurant business, the limited supply of necessary premises and high financial risks, the limited number of foreign suppliers of products. In addition, enterprises did not pay enough attention to managerial tasks, namely: the correct distribution of tasks, rational use of resources, marketing activities and strategic planning. As a result of military actions on the territory of Ukraine, part of the enterprises was destroyed, the other part was relocated to the western regions. Along with this, there was a reduction in demand and a limitation of labor resources. Security requirements of enterprises have become especially important. In addition, shelling of the energy infrastructure, which endangers all economic activity, became a challenge. For future recovery, enterprises need to take care of compliance of enterprises with international requirements, including for receiving aid. In order to receive financing from international donors, it is advisable for enterprises to create industry associations.